2022
DOI: 10.3389/fimmu.2021.747408
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Activation Scoring Model Assists in Chemotherapeutic Agents’ Selection and Mediates Cross-Talk With Immunocytes in Malignant Glioblastoma

Abstract: Gliomas are aggressive tumors in the central nervous system and glioblastoma is the most malignant type. Ferroptosis is a programmed cell death that can modulate tumor resistance to therapy and the components of tumor microenvironment. However, the relationship between ferroptosis, tumor immune landscape, and glioblastoma progression is still elusive. In this work, data from bulk RNA-seq analysis, single cell RNA-seq analysis, and our own data (the Xiangya cohort) are integrated to reveal their relationships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
(69 reference statements)
1
19
0
Order By: Relevance
“…Sensitivity to A.770041, AMG.706, ABT.888, AP.24534, AS601245, AUY922, and AZ628 was higher in the low-risk group than the high-risk group, while sensitivity to axitinib, A.443654, AG.014699, AICAR, Akt inhibitor VIII, and ATRA was higher in the high-risk group than the low-risk group. These drugs are commonly used in the clinical treatment of gliomas, and our results support their therapeutic value in this context ( Djuzenova et al, 2012 ; Yuan et al, 2018 ; Wang et al, 2021c ; Milton et al, 2021 ). In addition, these findings suggest the prospect of targeting lncRNAs in therapy for patients with gliomas.…”
Section: Discussionsupporting
confidence: 81%
“…Sensitivity to A.770041, AMG.706, ABT.888, AP.24534, AS601245, AUY922, and AZ628 was higher in the low-risk group than the high-risk group, while sensitivity to axitinib, A.443654, AG.014699, AICAR, Akt inhibitor VIII, and ATRA was higher in the high-risk group than the low-risk group. These drugs are commonly used in the clinical treatment of gliomas, and our results support their therapeutic value in this context ( Djuzenova et al, 2012 ; Yuan et al, 2018 ; Wang et al, 2021c ; Milton et al, 2021 ). In addition, these findings suggest the prospect of targeting lncRNAs in therapy for patients with gliomas.…”
Section: Discussionsupporting
confidence: 81%
“…Increased expression of ferroptosis-promoting genes was detected in the GBM necrotic area (17). Ferroptosis-related genes were also linked to immunosuppressive microenvironment and poor prognosis of GBM (18)(19)(20)(21)(22). These studies suggested that ferroptosis is involved in the development of a necrotic core in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Since ferroptosis was first defined, its function in cancer progression, chemotherapy, and immunotherapy has attracted great attention [ 51 ]. Increasing evidence indicates that iron-dependent programming death plays a vital role in shaping the cancer microenvironment and regulating antitumor immunity [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%